Kesulitan Berhitung pada Siswa Kelas 2 SD Negeri 45/I Sridadi - Mursyida, Aveny Kurnia; Ginting, Jane Fadilla Br; Aprillia, Novit; Kurnia, Nurul Izzah (MASALIQ, 2023)
Arithmetic difficulties among second-grade students at SDN 45/I Sridadi have captured the attention within the context of elementary education. Arithmetic is a fundamental skill that provides a crucial foundation for understanding more complex mathematical concepts in the subsequent levels. Nonetheless, many students encounter challenges in mastering arithmetic concepts at this level. This research aims to identify the factors contributing to arithmetic difficulties among second-grade students and propose appropriate teaching strategies to address these challenges. The research methodology employed includes observational studies and interviews with teachers and second-grade students at SDN 45/I Sridadi. The findings reveal that several factors contribute to students' arithmetic difficulties, including less diverse teaching methods, inadequate understanding of basic concepts, and variations in individual learning speeds. These obstacles may impact students' self-confidence and reduce their interest in learning mathematics. Based on the research findings, several effective teaching strategies are proposed. An inclusive and student-centered approach is recommended, which pays special attention to each student's individual needs and learning styles. The use of interactive learning media and role-playing in mathematics instruction can enhance students' engagement and participation. In addressing arithmetic difficulties, the roles of teachers and parents are crucial. Teachers can adopt creative and problem-based approaches to teaching mathematics, while parents can support learning at home by involving their children in everyday arithmetic activities. This research is expected to contribute to the field of education, particularly in tackling challenges related to arithmetic difficulties among second-grade students at SDN 45/I Sridadi. With a deep understanding of the contributing factors and effective teaching strategies, it is hoped that each student can overcome their arithmetic hurdles and achieve optimal progress in their mathematical learning.